(untitled) (Research, Society and Development, 2021)
Introduction: Excessive fat expansion during obesity causes fat dysfunction and inflammation to increase systemic levels of pro-inflammatory factors. The problem arises when, as a result of sustained obesity, the inflammatory response does not reach its objective and is not resolved, changing from a local reaction to a chronic systemic state, which can damage the individual’s brain functions. Objective: to explore how the inflammatory process corroborated by obesity could be associated with brain abnormalities, including dementia. Methodology: This is a descriptive research of the integrative literature review type. The research was conducted through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services databases, in August 2021 Results and discussion: Diet-induced obesity significantly exacerbates AD-like neuropathology and worsens cognitive impairment. Evidence shows that a high-fat diet is a risk factor for developing neuropathy and autonomic polyneuropathy, which may be due to chronic dysfunction secondary to obesity and inflammation due to the accumulation of macrophages and increased pro-inflammatory cytokines in peripheral nerves. seen a reduction in hippocampal volume and atrophy of the frontal, temporal and subcortical regions. Conclusion: This study does not establish that extra fat around the waist is the cause of dementia, it only suggests a link between these two characteristics.